Exploring the Role of Social Networks in Facilitating Health Service Access Among Low-Income Women in the Philippines: A Qualitative Study. (January 2022) - Luu, Kathy; Brubacher, Laura Jane; Lau, Lincoln L; Liu, Jennifer A; Dodd, Warren
Despite efforts to implement universal health care coverage (UHC) in the Philippines, income poor households continue to face barriers to health care access and use. In light of recent UHC legislation, the aim of this study was to explore how gender and social networks shape health care access and use among women experiencing poverty in Negros Occidental, Philippines. Semi-structured interviews were conducted with women (n = 35) and health care providers (n = 15). Descriptive statistical analyses were performed to report demographic information. Interview data were analyzed thematically using a hybrid deductive-inductive approach and guided by the Patient-Centred Access to Health Care framework. Women's decisions regarding health care access were influenced by their perceptions of illness severity, their trust in health care facilities, and their available financial resources. Experiences of health care use were shaped by interactions with health professionals, resource availability at facilities, health care costs, and health insurance acquisition. Women drew upon social networks throughout their lifespan for social and financial support to facilitate healthcare access and use. These findings indicate that social networks may be an important complement to formal supports (eg, UHC) in improving access to health care for women experiencing poverty in the Philippines.